Curbing commercialisation of human organs in Malaysia: Is the 'Opt-out' system a feasible solution? - Mohd Zaini, Nur Farha; Jahn Kassim, Puteri Nemie (2018)
As organ transplantation continues to save and improves the quality of lives of millions of people each year, the demands for human organs has been rising tremendously. The low rate of organ donation has created a huge gap between the supply and demand for human organs. This phenomenon has triggered unethical practices involving commercialization of human organs particularly, from living and unrelated donors. To increase the availability of organs for transplantation and curbing organ trafficking, many jurisdictions have introduced procedures and systems to increase the supply of human organs in their countries. Amongst the systems that have been implemented is ‘the opt-out’ system in which a person is deemed to have consented to becoming an organ donor unless he explicitly stated his objection otherwise. However, there are many arguments against and for the implementation of the ‘opt-out’ system that have been put forward. For Malaysia, which is currently adopting the ‘opt-in’ system, a change to the ‘opt-out’ system would be a radical move and require thorough considerations from a variety of perspectives including the religious and cultural sensitivities. For an ‘opt-out’ system to have a significantly positive impact on the national organ donation rate, efficient administrative mechanisms need to be in place, which include a transplant co-ordination network that works both locally and nationally as well as improving the quality of public information available about organ donation. A system that is nationally coordinated with effective structures would ultimately make a high rate of organ donation a possibility.